Penerapan Model Student-Centered Learning di Lembaga Pendidikan Tenaga Kependidikan - Elizar Elizar (Edukasi Lingua Sastra, 2017)
Teaching model is important componen in education system. It helps education process in implementing the aim of education effectively an effeciently. So, every education must also be creative in selecting and using education model. Based on the past and todays experiences, quality of education in Indonesia showed that the quality of teaching and learning process done by teachers and students was still low. Learning paradigm still focused on a teacher only (teacher centered learning) that caused learning process unattractive and monotonous. There were some factors that made difficult to change teacher paradigm in teaching and learning activity, namely teacher’s low commitment and skill in implementing active teaching-learning process. Therefore, teachers training institution (LPTK) should prepare the students to have skills in implementing active teaching and learning. One of some efforts that could be done to improve students’ skill, as prospective teachers, in implementing an active learning was that by implementing SCL (Student Centered Learning). It covered modelling a lecturer as a model in implementing active learning in the class and it integrates active learning in small group discussion, role-play and simulation, case study, discovery learning, self-directed learning, cooperative learning, colloborative learning, contextual learning, project based learning, problem based learning and inquiry.